Rhetorical Devices in the Poem "Endama yagheb ALbayan" by Ahmed Jarallah: An Analytical Study - khuncha sabah ahmed (Zanco Journal of Human Sciences, 2025)
This research examines the poem "When Expression Vanishes" by the poet Ahmad Jarallah through an analytical rhetorical study, which has established a significant impact in the record of Arabic poetry in the genre of elegy. The study aims to achieve a reading of the words and meanings of the selected poem, which includes the elegy of Professor Dr. Ahmad Fathi Ramadan, may God have mercy on him, utilizing a descriptive analytical approach through an introduction and three sections. The introduction of the research covers the problem statement, reasons for choosing the research topic, its importance, objectives, previous studies, methodology, and the research plan. In the first section, the researcher discusses the methods of meaning in the poem "When Expression Vanishes". The second section deals with the rhetorical methods in the poem of meanings when expression vanishes, and the third section covers the methods of embellishment in the poem "When Expression Vanishes", followed by a conclusion summarizing the most important research findings, and a bibliography of sources and references. The research reached several conclusions, including revealing the significance of the poem "When Expression Vanishes" by the poet Ahmad Jarallah, and the extent to which it expresses his sorrow and pain over the death of his mentor, Professor Dr. Ahmad Fathi, may God have mercy on him. The poem is rich in stylistic constructions through the study of semantics, and the multitude of rhetorical imagery such as simile, metaphor, metonymy, and implied metaphor, and how the poet employed these to express his grief and sorrow over the separation between the lover and the beloved scholar. The poem is also characterized by antithesis and contrast, as the poet wanted to clarify in his poem praise for the deceased; the contradiction clarifies and emphasizes the meaning. The words of the poem are dominated by simplicity, clarity, sweetness, sincerity of emotion, among other results.